Konsep BUMN Sebagai Objek Sengketa Administrasi Pemerintahan (Paradigma Baru Pasca UU No. 30 Tahun 2014 Tentang Administrasi Pemerintahan dan Telaah Kritis Terhadap RUU BUMN) - Muklis Al’anam (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
State-Owned Enterprises (BUMN) are companies owned by the state, where their capital comes from state assets that are separated for the purpose of generating state revenues. Unlike private companies, BUMN are not solely focused on profit-seeking but also have an essential role in fulfilling government duties, such as implementing policies for distributing subsidized goods to the public. This dual role means that BUMN are not only subject to the provisions of corporate law, as regulated in Law No. 40/2007 on Limited Liability Companies, but also bound by general administrative law. As a result, the concept of BUMN has evolved beyond merely a profit-driven state enterprise. It has become a public law entity responsible for formulating and implementing policies in the area of public services, which benefit the society at large.This legal research uses a combination of a statutory approach, conceptual approach, and case approach to explore the legal status of BUMN. The findings indicate that BUMN, in carrying out their activities, serve as public law entities, with nearly all of their business operations involving aspects of public services. Thus, BUMN should be understood as state administrative agencies or officials. Additionally, any financial losses incurred by BUMN are regarded as state financial losses under the relevant laws and regulations, emphasizing the interconnection between the state and BUMN in their implementation of public duties and services.